New records of long-legged flies (Diptera, Dolichopodidae) from Tyva Republic (Russia, Siberia) - I. Ya. Grichanov (Acta Biologica Sibirica, 2018)
During a 2017 survey conducted in the Tyva Republic of Russia, 322 specimens of Dolichopodidae have been collected. All 36 identified species are recorded for the first time in the Tyva Republic, including two probably undescribed species. Asyndetus longicornis is a new species for Siberia; Mongolian Melanostolus longipilosus and Thinophilus setosus are found for the first time in Russia. In total, 16 genera and 41 (including three unnamed) species are known from Tyva.